PRIDOBIVA JE Z A JA IZ BESEDIL I SLIK (Philological Studies, 2019)
As numerous empirical studies consistently prove, the addition of a suitable picture to a text greatly speeds up learning and improves retention of material (Mayer 2005; Salomon 1994). As Weidenmann (1989) shows on the basis of a review of 48 experimental studies, illustrated texts have an advantage from the point of view of learning and retention. Test subjects who were presented with an illustrated text achieved scores that were on average 36 % higher than test subjects who had merely read or listened to a text. This effect appears with a wide variety of texts, pictures and tasks and with different types of learners. The advantages of illustrations for the acquisition of knowledge are based either on the simplification of the complex or on the presentation of the abstract in a more concrete manner; the two principles are not however equally suitable for the tackling of various tasks such as identification, classification, remembering sequences and patterns, problem solving, construction of mental models, structuring the content of a text, etc. This paper deals with the functions of pictures and the use of various types of pictorial presentation in different tasks.